2023
DOI: 10.1136/bmjopen-2022-068963
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of brief psychosocial support for patients with cancer and their relatives: a quasi-experimental evaluation of cancer counselling centres

Abstract: ObjectivesThe aim of this study was to evaluate the effectiveness of brief psychosocial support for patients with cancer and their relatives regarding their mental health.DesignQuasi-experimental controlled trial with measurements at three time points (baseline, after 2 weeks and after 12 weeks).SettingThe intervention group (IG) was recruited at two cancer counselling centres in Germany. The control group (CG) included patients with cancer or relatives who did not seek support.ParticipantsIn total, n=885 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Here, too, no significant differences in measures of depression, anxiety, and HRQoL were found over a 4-month period, although the counseling services were rated positively. On the other hand, Lingens et al showed that depressive symptoms, HRQoL, and well-being were improved in cancer patients by brief psycho-social support [ 42 ]. But, our results should not be misinterpreted as ineffectiveness of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Here, too, no significant differences in measures of depression, anxiety, and HRQoL were found over a 4-month period, although the counseling services were rated positively. On the other hand, Lingens et al showed that depressive symptoms, HRQoL, and well-being were improved in cancer patients by brief psycho-social support [ 42 ]. But, our results should not be misinterpreted as ineffectiveness of the intervention.…”
Section: Discussionmentioning
confidence: 99%